(untitled) (SCIENCE TIME JOURNAL, 2026)
This article analyzes the impact of intercultural differences on the language and translation process, as well as the main errors occurring when translating terms. In the context of global communication, the correct expression of concepts belonging to different cultural contexts appears as an important task for the translator. The study examines the semantic, pragmatic, and cultural characteristics of terms based on a lingo culturological approach, identifying factors leading to incorrect translation such as the problem of equivalence, differences in cultural realities, insufficient consideration of context, and inconsistencies in terminological standards.